Relative time and life course research - Sánchez Mira, Núria; Bernardi, Laura (Cham, Switzerland: Springer, 2022)
Life course research (LCR) is intrinsically temporal, but this literature often draws on an unproblematized and undertheorized treatment of time (Wingens & Reiter, 2011). Time in mainstream LCR, particularly when taking a quantitative approach, is viewed as a marker—a container where changes can occur and through which they can be tracked—but not a matter of examination itself. Time is generally under stood as a linear and unidirectional construct, tied to the chronological clock and calendar, proceeding at a uniform pace, and providing an analytical frame for the phenomena under study without being part of them. In this way, time becomes a reified, absolute structure to pigeon-hole life course processes. Chronological time and age are indicators of underlying social and psychological phenomena in various life domains and their dynamic association. A linear understanding of time is also generally linked to an understanding of causality where causes lead to consequences in an orderly sequence. Yet, linearity, unidirectionality and uniform pace do not correspond to the way in which individuals experience time in their lives (Strauss, 1997 [1959]; Neale, 2019). Contemporary social science commonly acknowledges that time is multiple and diverse, including natural time, social times and lived times (Adam, 1990). As in physics, time is relative because it depends on the position and disposition of the observer (Rovelli, 2018). Under a relative perspective, time is not merely an external structure within which lives unfold but is subjectively defined and context dependent. The notion that time has a dual nature, one absolute and universal and one relative and subject or context-dependent, is a common theme in temporal theorizing. This is so from the classic distinction drawn by Aristotle in the Physics (book IV, 10–14) between the abstract Chronos-time and a meaningful Kairos-time (Rämö, 1999), to more recent distinctions between objective and inner time (Schutz, 1962) or events in time and time in events (Adam, 1990). All such distinctions refer to the fact that there would be an absolute, universal measurable time and a perceived, relative array of times and they are both useful in understanding the unfolding of events and transitions for they all feed into empirical realities. Many disciplines ranging from philosophy to neuroscience, including sociology, economics, psychology, or narrative studies, are confronted with the issue of how to account simultaneously for absolute and relative time. That is, how to account for the objectivized, chronological, and linear passage of time in the physical world of events, and the experiential, subjective perceptions of time in human understanding. Such ideas have been developed in parallel across disparate literatures and have now achieved a wide currency in social research. Yet, much LCR, particularly in the quantitative tradition, appears impermeable to these discussions and it has predominantly, although not exclusively, used an absolute conception of time. This chapter highlights the need for a more comprehensive and explicit theoretical conceptualization of time in LCR and we argue for a broader vision that goes beyond an absolute understanding of time to encompass notions of relative time. We propose a novel tripartite conceptualization of relative time that integrates interdisciplinary insights to define the multidirectional, elastic, and telescopic nature of time as its key characteristics. We argue that incorporating relative time alongside and in interaction with absolute time into LCR is necessary to understand the temporal processes that shape lives.
Keywords: Agency Time Life Course